An RNA polymerase II construct synthesizes short-hairpin RNA with a quantitative indicator and mediates highly efficient RNAi - Zhou, Hongxia (Oxford University Press, 2005)
RNA interference (RNAi) mediates gene silencing in many eukaryotes and has been widely used to investigate gene functions. A common method to induce sustained RNAi is introducing plasmids that synthesize short hairpin RNAs (shRNAs) using Pol III promoters. While these promoters synthesize shRNAs and elicit RNAi efficiently, they lack cell specificity. Monitoring shRNA expression levels in individual cells by Pol III promoters is also difficult. An alternative way to deliver RNAi is to use Pol II-directed synthesis of shRNA. Previous efforts in developing a Pol II system have been sparse and the results were conflicting, and the usefulness of those Pol II vectors has been limited due to low efficacy. Here we demonstrate a new Pol II system that directs efficient shRNA synthesis and mediates strong RNAi at levels that are comparable with the commonly used Pol III systems. In addition, this system synthesizes a marker protein under control of the same promoter as the shRNA, thus providing an unequivocal indicator, not only to the cells that express the shRNA, but also to the levels of the shRNA expression. This system may be adapted for in vivo shRNA expression and gene silencing.